The female subject in the Salvadoran modernist short story: a reading of its construction and cultural implications - Barquero Matamoros, Daniela (2021)
The article analyzes the representation of women in an innovative context such as that of the Salvadoran modernist short narrative to study the construction of female characters, their corporeal-ideological configuration, and the articulation of female social roles in the texts. It is determined that the model of woman constructed in the stories is analogous to that of modernism at the Hispanic American level, always from the censoring eye of the male subject. The woman appears as a voiceless individual, ideologically conceived as an object that can be killed and possessed by her male partner. Regarding social roles, they are configured as wives or mothers, with no place in public space. All this shows the generation and survival of a culture of violence against the female subject due to the conjuncture of machismo and the patriarchal structure.